NANO-MECHANICAL CHARACTERISTICS OF WEAR RESISTANT PVD COATINGS IN RELATION TO WEAR PERFORMANCE OF CUTTING TOOLS DURING HARD END MILLING OF H13 TOOL STEEL - Kornberg, Anton Benjamin (My University, 2015)
Two families of PVD hard coatings were successfully used for high performance end milling of hardened H13 tool steel. The first family of coatings are AlCrN-based, they are used for wet machining and the other family is based on TiAlCrSiYN coating and are used for dry machining of H13. It was shown that there is a strong potential for further advancement in the wear performance of the coatings by improving the coating architecture as well as by varying the deposition parameters used during their synthesis. A number of deposition parameters of the coatings show a strong impact on wear performance of the cutting tools. Wear performance was related to the structure and a number of nano-mechanical characteristics of the coating layer assessed using the NanoTest system produced by Micro Materials. It was shown that critical characteristics like nano-hardness, loading support factor and nano-scaled scratch resistance can be used to predict the wear performance of a cutting tool.
Keywords: PVD; loading support; nanoindentation; nano-scaled scratch